Oxford Urdu ka guldasta- gule lala - 5 - Farooqui, Fouzia Ahsan (Karachi Oxford university press, 2021)
*Oxford Urdu Guldasta: Gul-e-Lala Book 5* is a comprehensive Urdu language textbook designed to enhance language skills, cultural understanding, and literary appreciation among primary students. It features a carefully curated selection of prose, poetry, and exercises that promote vocabulary development, grammar proficiency, and creative expression. The book also incorporates activities that encourage critical thinking and a deeper connection with Urdu literature and heritage.